A Competencies Development as Innovative Project Supervisor through the Professional Learning Community - MANEELAM, PRATUENGSOOK (Journal of Teacher Professional Learning Community (JTPLC) (Online), 2022)
This research aimed to 1) examine status quo of teacher competency on innovation project supervising, 2) develop teacher competency on innovation project supervising through the KKUDS Modinadeng professional learning community (PLC). Methodology was action research. The method included two loop of action research. Each loop consists of 4 steps including 1) planning, 2) action, 3) observing, and 4) reflection. The action research loop was handled through school supervision. The participants included 9 science and technology teachers who volunteer to join the research project. Research instruments included teacher interview, test, observation form, evaluation form, and supervision form. Data analysis provided descriptive statistics and content analysis. The findings revealed the key features of developing teacher competency on innovation project supervising. Firstly, there were problems of organizing teaching and learning about developing the innovation projects because teachers lack of understanding and skills of innovation project supervising. Secondly, the paper highlighted the framework of developing teacher competency on innovation project supervising through PLC in context of coaching and supervising. Thirdly, the result of developing teacher competency revealed that most of teachers held good level of competency on innovation project supervising.